Clinicopathological spectrum of uterine leiomyomas in a state of Northern India: a hospital based study - Lahori, Mega; Malhotra, Aneeta Singh; ., Sakul; Khajuria, Arvind; Goswami, KC (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Myometrial lesions form a diverse group amongst which leiomyoma is the commonest visceral neoplasm affecting females in the reproductive age group. They are noted clinically in 20-30% of women over 30 years of age; are rare prior to the menarche, common in reproductive life and have a tendency to regress after the menopause. Their gross appearances are often altered by various secondary changes. Subtypes of leiomyoma are chiefly of interest as they may mimic malignancy in some cases. Methods: All the hysterectomy and myomectomy specimens which were received in the department of pathology, ASCOMS hospital Jammu, Jammu and Kashmir over a period of one year, out of which 79 cases with leiomyomas were included in the study. The specimens were properly labeled, fixed (in NBF), examined grossly, processed, stained and examined microscopically. Results: Age range of the patients with leiomyoma was18-62 years. Majority of the patients were between 41-50 years (46.84% cases). Menorrhagia was the commonest symptom constituting 37.97% cases and fibroid uterus was the most common clinical diagnosis provided (44%). Most common location of leiomyoma’s was intramural (57.43%) followed by subserosal (30.69%). 56.96% leiomyoma’s were single and 43.04% were multiple. Degenerative changes were observed in 16.46% cases, amongst which hyaline change was the most common (6.33%). 9 types of leiomyoma variants were seen, amongst which cellular leiomyoma (6.33%) was the commonest. Adenomyosis was associated with leiomyoma in 19.23% cases. Conclusions: This study was conducted to analyze the clinic pathologic spectrum of uterine leiomyoma’s in northern India with regards to their clinical presentation, associated changes and variants, and to compare our findings with similar studies from different parts of the world.